Rethinking the `back to wilderness' concept for Sundaland's forests - Giam, X.; Clements, G.R.; Aziz, S.A.; Chong, K.Y.; Miettinen, J. (Elsevier, 2011)
Traditional biodiversity conservation approaches emphasize the protection of pristine forests. However, it has become increasingly difficult to secure large tracts of undisturbed forests, particularly in the developing tropics. This has led some conservation scientists and organizations to explore the conservation potential of human-modified habitats, such as selectively logged forests. On the other hand, other scientists have highlighted the perils of overselling the conservation value of degraded habitats and advocate for re-focusing of efforts and resources on protecting primary forests. While there are merits to both contentions, we argue that the ``back to wilderness'' paradigm has limited relevance in the Sundaland region. This is because: (1) primary forest only makes up a small minority of the remaining forest in the region and most of it is already protected by law; (2) vast areas of selectively logged forest are still susceptible to plantation conversion; and (3) selectively logged forest are important habitats for some of the world's most endangered species. To meet both conservation and development goals, we suggest that tracts of selectively logged forest be assessed for their ecological value and forests of high conservation value be prioritized for better protection through their inclusion into existing protected area networks and/or improved sustainable forestry management. (C) 2011 Elsevier Ltd. All rights reserved.